Scientia Poetica : Jahrbuch für Geschichte der Literatur und Wissenschaften / Yearbook for the History of Literature, Humanities and Sciences (De Gruyter, 2012)
The yearbook has the task of applying the fields of literary and scientific history to one another. It offers a transdisciplinary discussion forum for the historical analysis of the interactions between the (natural) sciences and literature (studies) in theory development and reflection from the late Middle Ages to the present.